TINGKAT STRES IBU DALAM PENDAMPINGAN PEMBELAJARAN DARING ANAK SELAMA MASA PANDEMI COVID-19 - Yanti Yulianti; Denny Paul Ricky (NUTRIX, 2022)
Mother’s Stress Level in Assisting Children Online- Learning During Pandemic Covid-19 at Kecamatan Parongpong. Online learning in school-age children during Covid-19 pandemic has a special burden on mother and put they in a risk of stress. The purpose of this study is to determine the stress level of mother in assisting school-age children online learning during pandemic. The research design was quantitative descriptive. The sample of this study was 50 mothers of school-age children and obtained by random sampling method. Perceived Stress Scale (PSS-10) questionnaire were used for collecting data and analyzed by descriptive (univariate) analysis. The result showed the stress level of mother was in moderate stress. Mother's stress level is caused by several things, such as the various mother’s roles during pandemic, the mother's education background, family’s cost of living and cost of education during pandemic. The main factors influence the stress level of the mother need to be analyzed further for the next study. Keywords: Covid-19, Mother, Online learning, Stress level. Pembelajaran daring pada anak usia sekolah di pandemi Covid-19 memberikan beban tersendiri bagi ibu sehingga beresiko menimbulkan stres pada ibu. Tujuan penelitian ini adalah untuk mengetahui tingkat stres ibu yang mendampingi anak usia sekolah selama pembelajaran daring di masa pandemi. Desain penelitian ini adalah deskriptif. Sampel pada penelitian ini adalah 50 orang ibu yang mendampingi anak usia sekolah dalam pembelajaran daring yang didapatkan dengan metode random sampling. Data dikumpulkan dengan mengunakan kuesioner Perceived stres Scale (PSS-10) dan dianalisa dengan analisis deskriptif (univariat). Hasil penelitian menunjukkan bahwa tingkat stres ibu yang mendampingi anak usia sekolah dalam pembelajaran daring selama masa pandemi adalah stres sedang. Tingkat stres ibu disebabkan oleh beberapa hal seperti berbagai peran yang harus dilakukan ibu, tingkat pendidikan ibu, biaya hidup dan biaya pendidikan selama pembelajaran daring. Perlu dianalisis faktor yang sangat berpengaruh pada tingkat stres ibu yang mendampingi anak belajar dengan metode daring di masa pandemi. Kata Kunci: Covid-19, Ibu, Pembelajaran daring, Tingkat stres.